2000
DOI: 10.1148/radiology.215.3.r00jn48807
|View full text |Cite
|
Sign up to set email alerts
|

Brain Abnormalities in Gulf War Syndrome: Evaluation with1H MR Spectroscopy

Abstract: Veterans with different Gulf War syndromes have biochemical evidence of neuronal damage in different distributions in the basal ganglia and brainstem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
55
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 94 publications
(61 citation statements)
references
References 72 publications
4
55
2
Order By: Relevance
“…White et al [50] found that patients with pathologies associated with structures believed to be targets of neurotoxins-basal ganglia and white matter-exhibited notably higher false positives on the NES2 continuous performance task. Haley and colleagues [41,51] and Meyerhoff et al [52] have shown by using magnetic resonance spectroscopy that neuronal integrity, as reflected in N-acetylaspartate-to-creatine (NAA/Cr) ratio, was reduced in basal ganglia (in Haley Syndromes 1 and 2) and brainstem (in Haley Syndromes 2 and 3). Another study of GW veterans showed a dose-dependent correlation of DOD-modeled estimates of sarin exposure and reduction in white matter volume [5,53].…”
Section: Discussionmentioning
confidence: 99%
“…White et al [50] found that patients with pathologies associated with structures believed to be targets of neurotoxins-basal ganglia and white matter-exhibited notably higher false positives on the NES2 continuous performance task. Haley and colleagues [41,51] and Meyerhoff et al [52] have shown by using magnetic resonance spectroscopy that neuronal integrity, as reflected in N-acetylaspartate-to-creatine (NAA/Cr) ratio, was reduced in basal ganglia (in Haley Syndromes 1 and 2) and brainstem (in Haley Syndromes 2 and 3). Another study of GW veterans showed a dose-dependent correlation of DOD-modeled estimates of sarin exposure and reduction in white matter volume [5,53].…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance spectroscopy in patients with CFS has revealed a high choline/creatinine ratio, indicating increased levels of free choline, in areas of the central nervous system [23,24]. In GWS, however, the choline/creatinine ratio in brain structures is normal or depressed [25]. An increased choline peak on magnetic resonance spectroscopy is a reflection of abnormal membrane phospholipid metabolism and is normally associated with an infectious [26,27] or inflammatory state [28].…”
Section: Discussionmentioning
confidence: 99%
“…An increased choline peak on magnetic resonance spectroscopy is a reflection of abnormal membrane phospholipid metabolism and is normally associated with an infectious [26,27] or inflammatory state [28]. On the other hand, a reduced choline/creatinine ratio, as seen in GWS, indicates atrophy [29,30], late infarction [31] or neuronal damage to the brainstem [25]. These data reflect our present findings in the peripheral vascular endothelium, where the response to acetylcholine was increased in CFS and normal in GWS and in patients exposed to organophosphates.…”
Section: Discussionmentioning
confidence: 99%
“…Repeat administration of the questionnaire to 335 primarily US Army veterans of the 1991 Gulf War replicated the principal component structure, tested by confirmatory factor analysis [8] . Subsequent studies of representative ill veterans and well controls from the naval reserve battalion differentiated the 3 syndrome variants and controls on neuropsychological [10,11] , neurophysiological [10,12] , autonomic [13] , brain imaging [7,[14][15][16] and functional status [17] measures, with abnormalities severest and most widespread in factor syndrome variant 2 ( table 1 ). The 4 subgroups were particularly well differentiated by a discriminant function of changes in regional cerebral blood flow from a cholinergic pharmacological challenge, measured by single-photon emission computed tomography [7] ( fig.…”
Section: Methodsmentioning
confidence: 99%